2015
DOI: 10.1021/jacs.5b03370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Correlation of Substrate Position with Reaction Outcome in the Aliphatic Halogenase, SyrB2

Abstract: The iron(II)- and 2-(oxo)glutarate-dependent (Fe/2OG) oxygenases catalyze an array of challenging transformations, but how individual members of the enzyme family direct different outcomes is poorly understood. The Fe/2OG halogenase, SyrB2, chlorinates C4 of its native substrate, L-threonine appended to the carrier protein, SyrB1, but hydroxylates C5 of L-norvaline and, to a lesser extent, C4 of L-aminobutyric acid when SyrB1 presents these non-native amino acids. To test the hypothesis that positioning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
215
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(225 citation statements)
references
References 54 publications
8
215
2
Order By: Relevance
“…[44,232] Recent experiments fit well into the overall picture. [233] At the same time, it seems that intrinsic properties of the metal complex may also play a role here, as it was found that the synthetic [Fe IV (O)(TPA)Cl] + complex has an appreciable preference toward rebound to the ligand in the cis position with respect to the amine nitrogen of TPA, as a result of the different bond strengths. [234] However, it is noteworthy that the rebound reactivity/selectivity of low-weight synthetic complexes can be considerably influenced by radical escape from the solvent cage and its reaction with other species in solution.…”
Section: Chemoselectivitymentioning
confidence: 87%
“…[44,232] Recent experiments fit well into the overall picture. [233] At the same time, it seems that intrinsic properties of the metal complex may also play a role here, as it was found that the synthetic [Fe IV (O)(TPA)Cl] + complex has an appreciable preference toward rebound to the ligand in the cis position with respect to the amine nitrogen of TPA, as a result of the different bond strengths. [234] However, it is noteworthy that the rebound reactivity/selectivity of low-weight synthetic complexes can be considerably influenced by radical escape from the solvent cage and its reaction with other species in solution.…”
Section: Chemoselectivitymentioning
confidence: 87%
“…Some characterized examples include the nonheme dinuclear iron ribonucleotide reductase (RNR R2) (18,19) and mononuclear iron halogenase SyrB2 (20-22). The mechanisms for RNR and SyrB2 highlight the importance of quaternary structural elements, an extensive 35-Å proton-coupled electron transfer pathway in RNR (23), and extremely subtle (subangstrom) substrate positional tuning (SyrB2) (21,22), to enable efficient circumvention from the monooxygenation reaction coordinate.P450-I has also been linked to a number of important transformations in which an oxygen rebound step is not readily observed, including the desaturation of pharmaceuticals by liver P450s to afford hepatotoxic metabolites (24) and the C−C lyase activity of human P450 aromatase that is critical for estrogen biosynthesis (25), among others (26, 27). However, unambiguous determination of the oxidant responsible and operant mechanism for these aberrant P450 transformations has met significant challenges.…”
mentioning
confidence: 99%
“…Some characterized examples include the nonheme dinuclear iron ribonucleotide reductase (RNR R2) (18,19) and mononuclear iron halogenase SyrB2 (20-22). The mechanisms for RNR and SyrB2 highlight the importance of quaternary structural elements, an extensive 35-Å proton-coupled electron transfer pathway in RNR (23), and extremely subtle (subangstrom) substrate positional tuning (SyrB2) (21,22), to enable efficient circumvention from the monooxygenation reaction coordinate.…”
mentioning
confidence: 99%
“…Transposon mutagenesis performed by Xu and Gross (1988) and Zhang and Gross (1995) has proven that a chromosomal region larger than 25 kb is involved in the biosynthesis of SRE. Within this region, four genes, namely, syrB, syrC, syrD and syrP have been sequenced and partially characterized (Martinie et al, 2015;Singh et al, 2007;Gross, 1991;Zhang and Gross, 1997;Quigley et al, 1993). SyrD has similar sequence to the ATP binding cassette transporter superfamily, thus, it is hypothesized that syrD product is involved in the transportation of SRE across the cytoplasmic membrane (Quigley et al, 1993).…”
Section: Discussionmentioning
confidence: 99%